New compositional data supports a decentralized model of artefact production and circulation in the pre-columbian Andes - Lazzari, Marisa (2017)
The circulation and exchange of goods and resources at various scales have long been considered central to the understanding of complex societies, and the Andes have provided a fertile ground for investigating this process. However, long-standing archaeological emphasis on typological analysis, although helpful to hypothesize the direction of contacts, has left important aspects of ancient exchange open to speculation. To improve understanding of ancient exchange practices and their potential role in structuring alliances, we examine material exchanges in northwest Argentina (part of the south-central Andes) during 400 BC to AD 1000 (part of the regional Formative Period), with a multianalytical approach (petrography, instrumental neutron activation analysis, laser ablation inductively coupled plasma mass spectrometry) to artifacts previously studied separately. We assess the standard centralized model of interaction vs. a decentralized model through the largest provenance database available to date in the region. The results show: (i) intervalley heterogeneity of clays and fabrics for ordinary wares; (ii) intervalley homogeneity of clays and fabrics for a wide range of decoratedwares (e.g., painted Ci-naga); (iii) selective circulation of two distinct polychrome wares (Vaquer-as and Condorhuasi); (iv) generalized access to obsidian from one major source and various minor sources; and (v) selective circulation of volcanic rock tools from a single source. These trends reflect the multiple and conflicting demands experienced by people in small-scale societies, which may be difficult to capitalize by aspiring elites. The study undermines centralized narratives of exchange for this period, offering a new platform for understanding ancient exchange based on actual material transfers, both in the Andes and beyond.